2014
DOI: 10.1080/08952841.2014.906878
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Physical Activity and Perceived Health Status in Older Women: Findings from the Woman’s College Alumni Study

Abstract: Using data collected from the Woman's College (WC) Alumni Study, the purpose of this study was to determine whether perceived health status is related to physical activity in older women. A multiple linear regression analysis was conducted to examine the relationship between amounts of physical activity and self-reported health status. The results of the current study reveal that the level of physical activity is significantly correlated with perceived health status. The findings of this study have implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Learning to move aims to make someone capable and skilled in mastering movement, including mastering movement coordination. Regular and continuous physical activity is needed for coordination learning (Eifert, Wideman, Oberlin, & Labban, 2014;Langlois, Vu Tuong, Chassé, Dupuis, Kergoat, & Bhere, 2013;Paillard, Rolland, & Barreto, 2015). The end result of learning movement is the ability to do movement patterns of body skills, every movement learning goal generally has expectations with the emergence of certain findings, these findings are usually in the form of skill mastery.…”
Section: Discussionmentioning
confidence: 99%
“…Learning to move aims to make someone capable and skilled in mastering movement, including mastering movement coordination. Regular and continuous physical activity is needed for coordination learning (Eifert, Wideman, Oberlin, & Labban, 2014;Langlois, Vu Tuong, Chassé, Dupuis, Kergoat, & Bhere, 2013;Paillard, Rolland, & Barreto, 2015). The end result of learning movement is the ability to do movement patterns of body skills, every movement learning goal generally has expectations with the emergence of certain findings, these findings are usually in the form of skill mastery.…”
Section: Discussionmentioning
confidence: 99%
“…These findings give support to our hypothesis postulating better functional fitness results for the group of senior citizens living at home. While realizing the complexity of the process of ageing it may be concluded that regular and adequate physical activity is indispensable for healthy life-style (Eifert et. al., 2014, Langlois et.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there seems to be a number of factors other than leisure that conceivably contribute to health to varying extents. In particular, perceived health status in older adults has been found to be associated with sociodemographic characteristics such as sex, education, and income (Bryant et al, 2000;Machon et al, 2016;Schulz, Mittelmark, & Kronmal, 1994), chronic diseases (Eifert, Wideman, Oberlin, & Labban, 2014;Mavaddat, Vladeras, van der Linde, Khaw, & Kinmonth, 2014;Molarius & Janson, 2002), and functional status (Hoeymans, Feskens, van den Bos, & Kromhout, 1997;Latham & Peek, 2013). Additional factors linked to perceived health status are social relationships (White, Philogene, Fine, & Sinha, 2009;An, 2015), neighborhood environment (Mathis, Rooks, & Kruger, 2015;Subramanian, Kubzansky, Berkman, Fay, & Kawachi, 2006), alcohol consumption (Moriconi & Nadeau, 2015), and spiritual satisfaction (Daaleman, Perera, & Studenski, 2004;George, Larson, Koenig, & McCullough, 2000).…”
Section: Limitations In Understanding the Relationship Between Leisurmentioning
confidence: 99%
“…As outlined previously (Eifert et al, 2014), a total of 8,969 graduates with active addresses were initially identified as potential participants for the WC Alumnae Women's Health Study. A random sample of 1,818 alumnae where drawn from this list.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation